Between ubiquity and media convergence: communication and innovation in the football of Sport Club Internacional (Comunicação & Inovação, 2015)
The article aims to address the use of technologyin sport for analysis, improvement and enhancementof athletes, as it is with the Sport Club Internacional, of Porto Alegre (RS), which usesa software suite to analyze the players with potentialfor hiring by the club and a device (vest)with GPS for performance analysis of their athletesduring training. Thus, from documentary andbibliographical research, we aim to understand theoperating logic of these devices in the context ofdigitalization and virtualization of today's world.
Keywords: Communication. Innovation. Technology.